IgG4-related aortitis/periaortitis and periarteritis: a distinct spectrum of IgG4-related disease - Peng, Linyi; Zhang, Panpan; Li, Jieqiong; Liu, Zheng; Lu, Hui; Zhu, Liang; Wang, Xiaorong; Teng, Fei; Li, Xuemei; Guo, Huifang; Fei, Yunyun; Zhang, Wen; et al. (Arthritis research & therapy, 2020)
Large vessels could be involved in immunoglobulin (Ig)-G4-related disease (IgG4-RD). This study aimed to clarify the clinical features and evaluate the treatment efficacy for IgG4-RD with aortitis/periaortitis and periarteritis (PAO/PA). This study prospectively enrolled 587 patients with IgG4-RD with a follow-up time of more than 6 months. The distribution of IgG4-related PAO/PA was classified into four types: type 1, thoracic aorta; type 2a, abdominal aorta; type 2b, abdominal aorta and iliac artery; type 2c, iliac artery; type 3, thoracic and abdominal aorta; and type 4, other arteries. Patient's demographic data, clinical characteristics, laboratory parameters, and treatment efficacy were analyzed. Of 587 IgG4-RD patients, 89 (15.2%) had PAO/PA. The average age was 58.3 ± 11.1 years, with male predominance (85.4%). Vessels affected were as follows: abdominal aorta (83.1%), iliac artery (70.8%), thoracic aorta (13.5%), and other vessels (13.5%). The most prevalent distribution type of IgG4-related PAO/PA was type 2b, with 74 (83.1%) patients, followed by type 2a, type 2c, type 3, and type 1. Fifty-five (61.8%) PAO/PA patients had hydronephrosis, with renal insufficiency occurring in 43 (48.3%), and 31 (34.8%) PAO/PA patients had D-J stent drainage due to severe ureteral obstruction. After treatment with a glucocorticoid and immunosuppressants, 82% patients achieved remission with shrinking of the perivascular mass by more than 30%. IgG4-RD with PAO/PA was distinct from non-PAO/PA in demographic features, organ involvement distribution, inflammatory markers, and serum IgG4 and IgE. The most common affected vessel was the abdominal aorta, and most patients responded well with treatment.